Program Peningkatan Pengetahuan Fiqih dengan Memakai Kitab Mabadil Fiqih Pada Masa Pandemi Covid-19 di Dusun Sumber Kepuh - Siti Mardiyah; Khoirotul Izzah (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2020)
Every education and learning both formal and non-formal certainly has a goal to be achieved. Education aims to help learners to develop humanitarian potentials. So that the task of educating must be done correctly and on purpose. The environmental situation due to the Covid-19 pandemic is not something that discourages children from studying the book of Mabadi Fiqh. The Book of Mabadil Fiqh is a book that contains islamic sharia teachings on the pillars of Islam, faith, the procedure of worship wudlu, prayer, zakat, fasting, hajji and elements that cancel it and so on. Please note that to increase the child's knowledge is not enough from school alone but there must be other assistance. And can be used as motivation in seeking knowledge that does not know the time and place.